Implementasi Prinsip Syariah dalam Praktik Jual Beli Online Pada Aplikasi Tiktok Secara Live: Studi pada Mahasiswa Prodi Hukum Ekonomi Syariah Stis Al Wafa - Ardina, Cindy; Bianda, Ryan; Saputra, Refki (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to find out how online buying and selling practices in live TikTok application for STIS Sharia Economic Law study program students AL WAFA and to find out how to implement sharia principles in live online buying and selling on TikTok carried out by Law study program students STIS AL WAFA Sharia Economics. This study uses a qualitative method using interview techniques, observation and documentation. As for models The data analysis used is data collection, data reduction, presentation data and drawing conclusions. The results of this research show that in In practice, students buy and sell by ordering or shopping when the sellers are live so you can interact with the sellers directly to be able to show the desired item via live, and check out via the yellow basket provided by the seller when live takes place. In the process of buying and selling transactions on students' live TikTok STIS AL WAFA has implemented sharia principles in selling buy such as the principle of divinity (tauhid), the principle of willingness (antaradhin), principle expediency or benefit, principles of justice, principles of honesty, principles freedom, moral or ethical principles, finally valid principles.